Institutionnaliser la collaboration : planifier le recours aux approches collaboratives en environnement - Nicolas Milot (VertigO)
Civic society participation is more and more common in environmental and natural resources governance. A lot of experiences have shown the capacity of social actors to get involved in sustainable management processes. Consequently, many governments have developed recently governance models based on social actors cooperation. However, passing from a descriptive use of a new governance paradigm to its implementation is a complex task. In particular, the institutionalization of cooperation into environmental management processes could lead to some difficulties.In this paper, by the analysis of Quebec watershed management politic implementation, we present some reasons which highlight the complexity linked with cooperation institutionalization. Nevertheless, we suggest to use the concept of social organization to look at social actors cooperation in a prospective way and then, to influence the elaboration of new environmental policy based on cooperation. This perspective allow us to identity the challenges related to the generalization of cooperation as a major part of environmental policies.